Detection of Root Caries Using Laser-Based Detection Device - DIAGNOdent - Faizan Tariq; Ruhina Ali; Madiha Rasheed; Rabia SannamKhan (ziauddin University, 2020)
Introduction: Dental care for older population is becoming a matter of concern within the National health services (NHS) United Kingdom (UK) due to increasing life expectancy of older people and retention of their natural teeth. The aim of study was to relate the International Caries Detection and Assessment System (ICDAS) scores with severity index in order to detect root caries and DIAGNOdent readings, at an early stage, to manage these lesions non-invasively. Methods: Fresh 95 extracted teeth were collected from Oral Surgery and Dental Emergency Department at Barts and the London, Queen Mary University of London. In this in vitro study, 19 out of 95 teeth had root caries. Prior to recording the readings, extracted teeth were cleaned and polished. Each lesion underwent clinical examination. To detect root caries DIAGNOdent readings (ICDAS), severity index were obtained. Pearson's correlation coefficients tests were applied. Results: The correlation between cavitation and ICDAS scores shows the significant value of 0.01. The DIAGNOdent reading with momentum and peak values was 45.37 with standard deviation of 32.16 and for peak with the mean value of 49.79 and 31.72 of standard deviation. Regarding, readings of DIAGNOdent and severity index establishment of correlation was difficult to establish. The reason was score of severity index regarding specimen no.1 is 3.3 was illustrative of lesion that is leathery. Conclusion: The DIAGNOdent readings system did not support the detection of root caries. However, the severity index scoring system is in need of greater categories regarding caries of the root.